PERANCANGAN ULANG ALAT MESIN PEMBUAT ES PUTER BERDASARKAN ASPEK ERGONOMI - Adhi Dwi Arta; Rahmaniyah Dwi Astuti; Susy Susmartini (Performa: Media Ilmiah Teknik Industri, 2012)
Facts in the real condition is show that the little entrepreneur using the conventional devices in small village for make “es puter”, causes the worker have many complaint while making “es puter”. Appear this complaint can make musculoskeletal injury for the worker. As a result of this activity there are many complaints with the most dominant of complaints occur in the neck, arm, wrist, knee, and ankle.That injuries happen while revolve the ice tube, the process experience friction with ice in the outside of the tube. In this research have done identify desire and expectation of worker had done with interview, and the result is translated become necessity and become a concept of design device. The second phase is determinate device dimension base on anthropometric dimension. The last phase is making machining “Es Puter”. The result is “es Puter” machine with revolve mechanism using motor with 1400 rpm, is reduction became 70 rpm, and the production cost Rp 3.557.400,00. This device giving repair in processing position in making “Es Puter” then can decrease musculoskeletal injury, as well as ave safety, comfortable, and can shorten production time became 1 hour.